Good Corporate Governance Pengaruhnya Pada Kinerja Keuangan Perbankan Syariah di Indonesia - Lely Ana Ferawati Ekaningsih; Futhri Izza Afkarina (Politeknik Negeri Jember, 2021)
The implementation of GCG is very important in a bank to improve banking performance, especially the financial performance of Islamic banking. Financial performance is one of the tools used to measure whether the banking performance is going well or not. This study aims to analyze the effect of Good Corporate Governance (GCG)/X on financial performance (ROA)/Y. This type of research is quantitative, using secondary data. The population is all Islamic banks registered with the OJK. While the sampling technique used purposive sampling method, namely 8 Islamic banks which were then multiplied by 3 years until the final sample was 24 samples. The data analysis technique used simple linear regression analysis. The results of this study indicate that GCG has a significant effect on financial performance. This is evidenced by the composite average value of Islamic banking which has the predicate